Pedicled iliac bone flap grafting in the treatment of late presentation Legg–Calvé–Perthes disease - Xiao, Yong-bing; Du, Wei; Wu, Pan-feng; Qing, Li-ming; Yu, Fang; Tang, Ju-Yu (Frontiers in Surgery, 2023)
Background Legg–Calvé–Perthes disease (LCPD) is a juvenile form of ischemic femoral head osteonecrosis affecting children. The lack of effective and timely treatment results in severe sequelae in children (especially older ones). Although LCPD has been widely studied, little is known about its etiology. As a result, its clinical management is still challenging. This study will investigate the clinical and radiological results of patients older than 6 years and treated with pedicled iliac bone flap grafting for LCPD. Materials and methods A total of 13 patients (13 hips) with late presentation of LCPD were treated with pedicled iliac bone flap grafting. Of the 13 patients, 11 were male and 2 were female. The average age of the patients was 8.4 years (range 6–13). Preoperational radiographs and pain scores were analyzed for lateral pillar classification and the Oucher scale. The final follow-up radiograph was classified using a modified Stulberg classification. Limping, extremity length inequality, and range of motion were clinically assessed. Results The average follow-up of the patients was 70 months (range 46–120). During the surgery, seven hips were found to be lateral pillar grade B, two were grade B/C, and four were grade C. In the final examination, 12 hips were evaluated as good (Stulberg class I or II) and one as medium (Stulberg class III). There was limb shortening in one patient who was Stulberg class III. There was a significant difference between the preoperational and postoperational radiographic values and the Ocher scale, regardless of the surgical staging (P < 0.05). Conclusions Pedicled iliac bone flap graft can treat LCPD accompanied by pain and lateral pillar stage B, B/C, and C in children over 6 years. Level of Evidence Level IV—case series.